2014
DOI: 10.1111/lang.12054
|View full text |Cite
|
Sign up to set email alerts
|

Instructed Concept Appropriation and L2 Pragmatic Development in the Classroom

Abstract: In this article, we investigate the integration of concept‐based pragmatics instruction, grounded in Vygotskian sociocultural psychology, in an intact second‐semester French class (n = 13) over the course of an academic term. Our focus is on learners’ appropriation of the concepts of self‐presentation, social distance, and power with respect to the French second‐person pronoun system (i.e., tu versus vous) as revealed through language awareness questionnaires, appropriateness judgment tasks, and computer‐media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 18 publications
6
38
1
3
Order By: Relevance
“…The present study aligns with some recent pedagogical work that has shown that explicit instruction centered on the concepts of self‐presentation, social distance, and power can have an appreciable effect on learners’ understanding of, and ability to use, pragmatic features such as T and V (e.g., van Compernolle, , ; van Compernolle & Henery, ). The approach—concept‐based pragmatics instruction—aims to provide high‐quality explanations of categories of meaning, and how they are enacted through the use of T and V. The term high‐quality as used here refers to explanations that are based on current sociolinguistic and pragmatic research that goes beyond quantitative tendencies (i.e., conventions, frequencies of use) and explores the meaning and significance of sociolinguistic phenomena in the lives of people who use the language (see van Compernolle, , ch.…”
Section: L2 Pragmaticssupporting
confidence: 89%
See 4 more Smart Citations
“…The present study aligns with some recent pedagogical work that has shown that explicit instruction centered on the concepts of self‐presentation, social distance, and power can have an appreciable effect on learners’ understanding of, and ability to use, pragmatic features such as T and V (e.g., van Compernolle, , ; van Compernolle & Henery, ). The approach—concept‐based pragmatics instruction—aims to provide high‐quality explanations of categories of meaning, and how they are enacted through the use of T and V. The term high‐quality as used here refers to explanations that are based on current sociolinguistic and pragmatic research that goes beyond quantitative tendencies (i.e., conventions, frequencies of use) and explores the meaning and significance of sociolinguistic phenomena in the lives of people who use the language (see van Compernolle, , ch.…”
Section: L2 Pragmaticssupporting
confidence: 89%
“…Although the first study involving CBPI took place in a one‐on‐one tutoring context (van Compernolle, ), subsequent work (van Compernolle & Henery, ) has shown that the framework is feasible in a classroom setting. Focusing specifically on the concepts of self‐presentation, social distance, and power in relation to French tu and vous , van Compernolle & Henery () modified the CBPI framework to complement the existing syllabus for the class (e.g., content and themes) and in light of various time constraints. Monologic verbalizations were performed online in written form, and then the teacher led whole‐class instructional conversations in order to probe learners’ understandings and further support concept development.…”
Section: Concept‐based Pragmatics Instructionmentioning
confidence: 99%
See 3 more Smart Citations